Market Behavior in the Field of Insurance, Guarantee, and Pension Funds in the Indonesian Context: A Strategic Marketing Perspective - Siolemba Patiro, Shine Pintor; Damayanti, Prisila; Parwati, Azuarini Diah; Hendrian, Hendrian (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze market behavior in the insurance, guarantee, and pension fund sectors in Indonesia through a strategic marketing approach. These three sectors play a crucial role in the national financial system, yet face challenges in terms of market penetration, consumer trust, and adaptation to changing consumer behavior. Using descriptive qualitative methods and literature review, this study examines how industry players design and implement marketing strategies to address domestic market dynamics. Three grand theories are used in this study: the Resource-Based View (RBV) (Barney, 1991), Porter's Five Forces (Porter, 1980), and Diffusion of Innovations (Rogers, 2003). The results indicate that digital integration, personalized service approaches, and increased financial literacy are key factors in shaping consumer behavior and strengthening competitiveness. This study also highlights the importance of collaboration between regulators and industry players in creating a sustainable marketing ecosystem. The strategic implications of these findings provide guidance for policymakers and practitioners in formulating more effective strategies amidst the ever-evolving financial industry landscape.